Optimization for calibration of large-scale optical measurement positioning system by using spherical constraint - Zhao, Ziyue; Zhu, Jigui; Xue, Bin; Yang, Linghui (Journal of the Optical Society of America. A, Optics, image science, and vision, 2014)
The measurement accuracy of a large-scale optical measurement positioning system largely depends on the calibration procedure. A more reliable calibration approach for the system by using spherical constraints is presented in this paper, and both the adjustment model based on spherical constraint and the calculation method for the optimization are given. This approach can provide constraint in every direction of the system in the workspace and thereby estimate the orientation parameters more accurately than by using current methods. The experimental data show that by using the proposed method, which improves the accuracy of the depth direction, the average 3D coordinate error of the system compared with the laser tracker is about 0.18 mm in the whole workspace.